Developmental and Clinical Pragmatics (Handbooks of Pragmatics [HOPS] Ser., 2019)
This new landmark series provides a comprehensive overview of the entire field of pragmatics. It is based on a wide conception of pragmatics as the study of intentional human interaction in social and cultural contexts. In-depth articles discuss the foundations, major theories and most recent developments of pragmatics including philosophical, sociocultural and cognitive as well as methodological, contrastive and diachronic perspectives.